Socialization of Breast Self-Examination (BSE) Using Survivors with Non-Survivors in Women of Childbearing Age: Sosialisasi Pemeriksaan Payudara Sendiri (SADARI) Menggunakan Survivor dengan Non-Survivor Pada Wanita Usia Subur - Oki Alestari, Rena; Widia, Lidia; Devitasari, Ivana (KHD Production, 2023)
Cancer is one of the main causes of death throughout the world. 8.2 million deaths, one of which is caused by breast cancer. This is in accordance with the Indonesian Ministry of Health (2013) that breast cancer is a cause of death, and the incidence rate increases by 5% every year. Breast cancer is a solid cancer. According to Wibawa & Manuaba (2010) stated that cancer is a solid type of cancer. In Indonesia, breast cancer is the second most common cancer in women. The aim of this health outreach is for women of childbearing age to better understand early detection of breast cancer with breast self-examination (BSE). The service method uses counseling using lectures, questions and answers, and demonstrations using X booklets and leaflets as media for women of childbearing age which will be held on May 25, 2023, at the East Kotawaringin Plansian Village Office. The results of this community service activity can be said to be successful. This can be observed in the level of attendance and activeness of participants. This activity took place in an orderly and good manner without experiencing significant obstacles. The follow-up that needs to be done is to continuously provide information about early detection of breast cancer (BSE).